A New RMF Stirrer Using AISI4140 Mild Steel: Energy Optimization Application - Citak Hakan; Bicakci Sabri; Coramik Mustafa; Gunes Huseyin; Ege Yavuz (Electrical, Control and Communication Engineering)
This study examines the development of a novel FPGA-based RMF stirrer system. The system has been designed as a 3-phase system, with each phase being fed by PWM voltage with a phase difference of 120°. In case the system is driven at a 100 % duty cycle, the force acting on the magnetic fish remains continuous and constant until the subsequent phase changes. In such a case, at speeds under 400 rpm, the speed of the magnetic fish fails to be synchronized with the phase change speed. The magnetic fish, therefore, rotates more than 120° and the force is observed to cause a braking effect. Both fluid logic control (FLC) and virtual model control (VMC) were utilised to enable the system to be driven at a different duty cycle. The energy efficiency of the system for fluids with different viscosities has been attempted to be thereby improved with a lower current and shorter excitation time. With FLC and VMC control, the energy consumed by the system is reduced and the efficiency is increased, and approximately 95 % energy gain is obtained for liquids with viscosity up to 1.03 Pa·s. It has been experimentally proven that a lower limit value of the duty cycle of the PWM signal applied to the drive circuit of the system depends on the viscosity of the mixed liquid and a lower limit value increases with increasing viscosity. It has also been found that controlling the system with FLC and VMC does not have a great effect on the energy gain.